2013
DOI: 10.1115/1.4024569
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Fuel Cell Gas Turbine System Design and Optimization

Abstract: Ultrahigh efficiency, ultralow emission fuel cell gas turbine (FC/GT) hybrid technology represents a significant breakthrough in electric power generation. FC/GT hybrid designs are potentially fuel flexible, dynamically responsive, scalable, low-emission generators. The current work develops a library of dynamic component models and system design tools that are used to conceptualize and evaluate hybrid cycle configurations. The physical models developed for the design analysis are capable of off-design simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Others have reported that hybrid performance is very sensitive to decreasing U f . McLarty et al [32] reported a 15% decrease in system efficiency when dropping from 80% to 60% U f despite large increases in T IT . However, they conducted their design analysis using a series of parametric tests in which the operating conditions were varied one at a time rather than designing an optimum system for each.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have reported that hybrid performance is very sensitive to decreasing U f . McLarty et al [32] reported a 15% decrease in system efficiency when dropping from 80% to 60% U f despite large increases in T IT . However, they conducted their design analysis using a series of parametric tests in which the operating conditions were varied one at a time rather than designing an optimum system for each.…”
Section: Discussionmentioning
confidence: 99%
“…McLarty et al [32] reported an initial design system efficiency of 66% for coal syngas. This can be consistent with the results presented here of 75.6%, because the final optimized design performance would include the incremental influences of individual parameters such as U f , P r , T FC , η t , η c .…”
Section: Discussionmentioning
confidence: 99%
“…Due to elevated operating temperatures, SOFCs are fuel flexible and can be combined with conventional gas turbine power plants (hybrid systems). Previous analysis show that hybridization of existing fuel cell and gas turbine technologies canyieldultrahigh electrical efficiencies, in the range of65-75% [7][8][9]. These SOFC features are suited for distributed generation application, which can lead to widespread utilization of glycerol for electricity generation purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Fossil fuel consumption and emissions may be reduced by using solar-based technologies. For electricity generation, solar energy may be used directly (photovoltaic panels) or indirectly utilizing biofuels [3][4][5] applying, for example, fuel cell technology which additionally features high efficiency due to the direct transformation of chemical energy into electricity [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. However, the largest market for solar energy is now connected with the absorption of solar radiation to heat up media that are flowing through solar collectors.…”
Section: Introductionmentioning
confidence: 99%